Association between social determinants of health and olfactory dysfunction in older adults: A population‐based analysis. Issue 5 (2nd October 2022) - Stein, Eli; Chern, Alexander; Chen, Honglei; Shiroma, Eric J.; Devanand, D. P.; Gudis, David A.; Overdevest, Jonathan B.
Abstract: Background: Social determinants of health (SDoH) are environmental conditions that influence health outcomes. As olfactory dysfunction (OD) in older individuals is associated with increased morbidity and mortality, we sought to investigate the impact of specific SDoH on olfactory function. Methods: A cross‐sectional analysis of the Health, Aging and Body Composition Study, a US population‐based epidemiologic cohort study, was performed. Olfactory function was assessed utilizing both a self‐report and a psychophysical olfactory test (CC‐SIT test). Multivariable logistic regressions were performed to examine associations between specific SDoH with self‐reported anosmia (sOD) and objective anosmia (oOD) as assessed by psychophysical testing. Differences in sensitivity and specificity were evaluated with sample tests for equality of proportions. Results: Of 2219 participants, 13% had oOD and 18% had objective hyposmia; only 10% had sOD. Individuals identifying as Black race had higher odds of oOD (odds ratio [OR]:1.41, 95% confidence interval [CI]:1.02‐1.95), while females and those reporting family incomes ≥50, 000 had lower odds of oOD (OR: 0.46, CI:0.34‐0.62; OR:0.52, CI:0.29‐0.93), adjusting for covariates. No specific SDoH was significantly associated with sOD. The sensitivity and specificity of sOD for oOD was 23.1% and 92.0%, respectively. sOD had greater sensitivity in females than males (30.8% vs. 18.8%, p = 0.030), while specificity varied significantly depending on family income (range: 90.0%‐94.8%, p = 0.033). Conclusions: Utilizing a large population‐based study, we find disparities in the prevalence and self‐recognition of OD among individuals of different gender, race, and income levels. Further effort is needed to evaluate factors propagating these disparities and to raise awareness of OD across all patient populations.